Steatosis induced by nonylphenol in HepG2 cells and the intervention effect of curcumin. Issue 1 (13th December 2021) - Shan, Dandan; Wang, Jinming; Di, Qiannan; Jiang, Qianqian; Xu, Qian
Abstract : The first in vitro model of NP-induced steatosis in HepG2 cells was established. The mechanism may involve disruption of lipid metabolism and inhibition of the ROS-mediated AMPK/mTOR pathway. Curcumin may ameliorate the above changes. Abstract : Non-alcoholic fatty liver disease (NAFLD) has increasingly become a serious public health problem. There is growing evidence that nonylphenol (NP) exposure may cause steatosis, but the underlying mechanism is not fully understood. Curcumin (CUR) improves NAFLD-related lipid metabolism disorders and oxidative stress, but its preventive and therapeutic effects on NP-induced steatosis have not been reported. The objective of this investigation was to determine the capability and potential mechanism of NP to induce steatosis in vitro and the intervention of curcumin. HepG2 cells were treated with 0 μM, 20 μM, 30 μM, 40 μM NP for 24 h. Lipid droplets accumulated significantly in HepG2 cells after NP treatment, and the concentration of triglyceride (TG) and total cholesterol (T-CHO) increased significantly. Simultaneously, lipogenesis gene expression was up-regulated significantly, fatty acid oxidation (FAO) gene expression was significantly down-regulated, and reactive oxygen species (ROS) were overproduced. Meanwhile, the expression of p-AMPK/AMPK in the AMPK/mTOR signaling pathway was significantly down-regulated and the expression of p-mTOR/mTOR was markedly up-regulated. However, blocking ROS production with N -acetyl-l -cysteine (NAC) can reverse these phenomena. In addition, our study found that curcumin effectively ameliorated the effects of NP-induced steatosis. Our study indicates that NP can induce steatosis in HepG2 cells, and may be implicated in inhibiting the ROS-dependent AMPK/mTOR pathway, and that curcumin ameliorates the NAFLD-like changes induced by NP in HepG2 cells.